What we learned through asking about evidence: A model for interdisciplinary student engagement. Issue 1 (2nd January 2019) - Finlay, Jessica M.; Davila, Heather; Whipple, Mary O.; McCreedy, Ellen M.; Jutkowitz, Eric; Jensen, Anne; Kane, Rosalie A.
ABSTRACT: Traditional university learning modalities of lectures and examinations do not prepare students fully for the evolving and complex world of gerontology and geriatrics. Students involved in more active, self-directed learning can develop a wider breadth of knowledge and perform better on practical examinations. This article describes the Evidence in Aging (EIA) study as a model of active learning with the aim of preparing students to be effective interdisciplinary researchers, educators, and leaders in aging. We focus particularly on the experiences and reflections of graduate students who collaborated with faculty mentors on study design, data collection, and analysis. Students acquired new methodological skills, gained exposure to diverse disciplines, built interdisciplinary understanding, and cultivated professional development. The EIA study is a model for innovative student engagement and collaboration, interactive learning, and critical scholarly development. Lessons learned can be applied to a range of collaborative research projects in gerontology and geriatrics education.